Anti-phenolic glycolipid antibodies in Mycobacterium bovis infected cattle - Zijie Zhou; Anouk van Hooij; J. Hessel M. van Dijk; Nina Musch; Louise Pierneef; Hamza Khalid; Kees Franken; Thomas Holder; Neil Watt; Anita L. Michel; Jeroen D.C. Codée; Martin Vordermeier; et al. (One Health, 2025)
Mycobacterium bovis, the causative agent of bovine tuberculosis (bTB), causes significant financial losses in the agricultural industry. Additionally, M. bovis transmission from animals to humans can result in zoonotic TB, especially in low- and middle-income countries (LMICs), highlighting the need to enhance One Health surveillance to mitigate this threat.Antibodies directed against a major mycobacterial cell wall component of M. leprae, phenolic glycolipid-I (PGL-I), have shown excellent performance in identifying M. leprae infection in humans and animals. In this study, we therefore investigated whether antibodies against M. bovis PGL similarly represent a useful biomarker for M. bovis infection in cattle.Comparing sera from naturally M. bovis-infected and the single intradermal comparative cervical tuberculin test (SICCT)-negative cattle, we assessed the potential of M. bovis PGL antibodies to identify this mycobacterial infection. Our results show that serum levels of anti-M. bovis PGL IgG and -IgM in M. bovis-infected cattle were significantly higher than in the SICCT-negative cattle. The sensitivity for anti-M. bovis PGL IgM in infected animals was, however, moderate (44.9 %) and the false-positive rate was 6.3 % in SICCT-negative cattle. Notably, vaccination with BCG- or heat-killed M. bovis did not affect serum levels of anti-M. bovis PGL IgM in cattle. Moreover, none of the 57 anti-M. bovis PGL-seropositive cattle tested positive in the anti-M. leprae PGL-I assay. This study shows for the first time that anti M. bovis PGL antibodies can be detected in infected cattle: anti-M. bovis PGL IgM is a highly specific, but moderately sensitive biomarker for M. bovis infection in cattle, showing potential for differentiate infected from vaccinated animals (DIVA). It could be a valuable component in a multi-biomarker approach for diagnosing bTB.